An aspect ratio agglomeration multigrid for unstructured grids - Li, Zongzhe; Wang, Zhenghua; Cao, Wei; Yao, Lu (International journal for numerical methods in fluids, 2013)
SUMMARY A robust aspect ratio‐based agglomeration algorithm to generate high quality of coarse grids for unstructured and hybrid grids is proposed in this paper. The algorithm focuses on multigrid techniques for the numerical solution of Euler and Navier–Stokes equations, which conform to cell‐centered finite volume special discretization scheme, combines vertex‐based isotropic agglomeration and cell‐based directional agglomeration to yield large increases in convergence rates. Aspect ratio is used as fusing weight to capture the degree of cell convexity and give an indication of cell stretching. Agglomeration front queue is established to propagate inward from the boundaries, which stores isotropic vertex and also high‐stretched cell marked with different flag according to aspect ratio. We conduct the present method to solve Euler and Navier–Stokes equations on unstructured and hybrid grids and compare the results with single grid as well as MGridGen, which shows that the present method is efficient in reducing computational time for large‐scale system equations. Copyright © 2013 John Wiley & Sons, Ltd. The four cell‐based agglomerated coarse grids for NACA0012 airfoil by the present method and MGridGen are shown. Top four is generated by the present method and the bottom is generated by the open library MGridGen.